Association between physical activity and costs in very mild to moderately frail community-dwelling older adults: a cross-sectional study - Gottschalk, Sophie; König, Hans-Helmut; Werner, Christian; Fleiner, Tim; Thiel, Christian; Büchele, Gisela; Schäufele, Martina; Rapp, Kilian; Dams, Judith (BMC public health, 2024)
Physical activity (PA) plays a vital role in maintaining the functional ability that enables well-being in older age (healthy aging), potentially also saving costs for the healthcare system and society. The aim of this study was to examine the association between PA and healthcare and societal costs in a sample of very mild to moderately frail older adults.
Online veröffentlicht: 8. Oktober 2024
Gesehen am 05.11.2025